Completed Suicide by Firearm in an Individual With the Agrammatic Variant of Primary Progressive Aphasia: Case Report - Patel, Deepal; Andersen, Shaun; Smith, Kyler; Ritter, Aaron (Frontiers in Neurology, 2022)
The agrammatic or nonfluent variant of Primary Progressive Aphasia (nfvPPA) is a form of Frontotemporal Dementia (FTD) that is characterized by progressive language dysfunction, poor sentence construction, and low verbal fluency. Individuals with nfvPPA have intact insight into their decline, which may manifest as frustration and hopelessness, and show signs of impulsivity and disinhibition. Little is known about suicide risk in this patient population. Here we describe a case of an 84 year-old male with nfvPPA who, over the course of his care, experienced a decline in language and motoric functioning which coincided with increasing irritability and impulsivity. Despite this significant decline, he denied depressive symptoms or showed any suicidal tendencies, and he seemed to be looking forward to future events. His suicide, committed with a handgun during what appeared to be a rather innocuous trip to the garage, came as a significant shock to his spouse, family, and his clinical care team. To our knowledge, this is the first reported case of completed suicide in a patient with the nfvPPA subtype of FTD. Though this patient demonstrated demographic risk factors for suicide (advanced age, retired military veteran with easy access to firearms) there is a lack of data regarding how FTD may have contributed. Retained insight especially seems to be a risk factor for suicide across all forms of dementia. Impulsivity may be key when considering suicidality amongst FTD patients. Additionally, this case demonstrates the importance of addressing gun safety as there are few guidelines around gun ownership in this patient population.